Schistosomiasis in Pregnant Travelers: A Case Series. Issue 2 (13th October 2014) - Ben‐Chetrit, Eli; Lachish, Tamar; Mørch, Kristine; Atias, Drorit; Maguire, Conor; Schwartz, Eli
Abstract : Background: Travel‐related acquisition of schistosomiasis in Africa is well established. Data concerning Schistosoma infection in pregnant travelers are lacking and treatment derives from studies in endemic regions. Methods: This study was a retrospective case‐series of pregnant patients who were infected with Schistosoma species. Data regarding exposure history, clinical presentation, diagnosis, treatment, and fetal outcomes were collected and analyzed. Diagnosis of schistosomiasis was based on serology tests and/or ova recovery. Results: Travel‐related schistosomiasis during pregnancy was diagnosed in 10 travelers (with 20 pregnancies). Of the 10 women, 4 pregnant travelers with recent exposure were treated during their pregnancy with praziquantel (PZQ). The course and outcome of pregnancy in these patients was uneventful, and treatment had no apparent adverse effects on either the mothers or their babies. Six asymptomatic women were diagnosed years after exposure. During this period, they gave birth to 13 babies. They were never treated with PZQ. Birth weights of their infants were significantly smaller as compared with those of the infants of the women who were treated during their pregnancy (median 2.8 vs 3.5 kg). One baby was born preterm. One patient had three miscarriages. Conclusion: This is the first case‐series of pregnant travelers with schistosomiasis. Although a small case‐series with possible confounders, it suggests that schistosomiasis in pregnant travelers can be treated. A trend of lower birth weights was observed in the infants of the pregnant travelers who were not treated. PZQ therapy during pregnancy was not associated with adverse pregnancy or fetal outcomes in those four cases. Our results emphasize the importance of screening female travelers of childbearing age with a relevant history of freshwater exposure. Further studies are needed to reinforce these recommendations.